Ciguatera Fish Poisoning in East Asia and Southeast Asia - Thomas Y. K. Chan (Marine Drugs, 2015)
In the coastal countries of East Asia and Southeast Asia, ciguatera should be common because of the extensive tropical and subtropical coral reefs along the coasts and in the neighboring seas with ciguatoxic fishes. An extensive search of journal databases, the Internet and the government websites was performed to identify all reports of ciguatera from the regions. Based on the official data and large published case series, the incidence of ciguatera was higher in the coastal cities (Hong Kong, Foshan, Zhongshan) of southern China than in Japan (Okinawa Prefecture). In Singapore, ciguatera appeared to be almost unknown. In other countries, only isolated cases or small case series were reported, but under-reporting was assumed to be common. Ciguatera may cause severe acute illness and prolonged neurological symptoms. Ciguatera represents an important public health issue for endemic regions, with significant socio-economic impact. Coordinated strategies to improve risk assessment, risk management and risk communication are required. The systematic collection of accurate data on the incidence and epidemiology of ciguatera should enable better assessment and management of its risk. Much more work needs to be done to define the size threshold for important coral reef fish species from different regions, above which the risk of ciguatera significantly increases.